Reclaiming the Abject: Witchcraft and the Sacrificial Femininity in Suspiria. Issue 3 (23rd March 2023) - Burnsed, Dorian
Witchcraft has long been associated with expressions of femininity and womanhood. Suspiria, both 1977 and 2018 versions, provide vivid pictures of female bodies as sacrificial bodies bound and restrained by notions of monstrous femininity. The focus on the occult creates spaces wherein female characters find strength and healing through both displays of independence and interconnectedness to other women. These films, read through second- and third-wave feminisms, reveal the struggle to assert female empowerment in a male-dominated world.